Analisis Kepuasan Pengguna Aplikasi Jenius Menggunakan Metode End User Computing Satisfaction dan Importance Performance Analysis - Trisya, Cintia Putri; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah; Fronita, Mona (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Jenius is a digital bank owned by BTPN since 2016 and licensed by OJK. The Jenius application allows users to make payments, transactions and save money in the form of long-term deposits. In 2023, Jenius will have 5.2 million users, up from 4.4 million the previous year. However, users still face a number of problems in accessing the application, such as stopped transactions, difficulty verifying to get the OTP code, and difficulty contacting customer service. This research aims to evaluate the level of user satisfaction with the Jenius application using the End User Computing Satisfaction (EUCS) and Importance Performance Analysis (IPA) methods. The research results indicate that the level of user satisfaction is correlated with a level of conformity of 83%, indicating that the Jenius application has met user expectations because it is in the very satisfied category. Based on GAP calculations, all indicators have a negative value with an average of -0.919375, an assessment of the Jenius application reveals a gap between the quality of the services offered and user expectations. IPA quadrant analysis identified Relevance (C1) and Consistency (A2) as aspects requiring improvement. To maintain user satisfaction, factors such as Information Availability (T2), Attractiveness (F1), Neatness (F2), Clarity (F3), and user ease of use (E2).